2003
DOI: 10.1177/0146167203253473
|View full text |Cite
|
Sign up to set email alerts
|

Daily Supportive Equity in Close Relationships

Abstract: Receiving support in committed relationships has frequently been associated with negative psychological outcomes in the recipient, such as increased distress. The authors hypothesized that these negative effects could be offset by support recipients' reciprocation of support, that is, by creating a sense of supportive equity. To investigate this hypothesis, the authors obtained daily reports of mood and of received and given emotional support from both partners in 85 couples throughout a 4-week period. Recipro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
277
2
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 309 publications
(300 citation statements)
references
References 26 publications
16
277
2
5
Order By: Relevance
“…To continue to better understand dyadic coping and support transactions, more needs to be known about mutual provided and received support, as well as conflict and tension among couples. Reciprocity is seen as one determinant of support provision (Cutrona et al, 1997;Gleason et al, 2003;Jung, 1990;Knoll et al, 2006a;Knoll et al, 2006b;Liang et al, 2001). Therefore, it would be valuable to obtain data that allow for a closer examination of such reciprocal effects (Kenny & Cook, 1999;Newsom, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…To continue to better understand dyadic coping and support transactions, more needs to be known about mutual provided and received support, as well as conflict and tension among couples. Reciprocity is seen as one determinant of support provision (Cutrona et al, 1997;Gleason et al, 2003;Jung, 1990;Knoll et al, 2006a;Knoll et al, 2006b;Liang et al, 2001). Therefore, it would be valuable to obtain data that allow for a closer examination of such reciprocal effects (Kenny & Cook, 1999;Newsom, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In prior studies (e.g., Gable et al, 2003;Reis & Carmichael, 2006), we collected daily diary reports of various interactive behaviors over several weeks in samples of married or cohabiting adults (e.g., ''I was physically affectionate toward my partner'' and, in parallel, ''My partner was physically affectionate toward me''). Findings in those studies revealed that for positive and supportive acts, hits predicted increased relationship well-being, whereas misses were unrelated to relationship well-being (see Gleason, Iida, Bolger, & Shrout, 2003;Gleason, Iida, Shrout, & Bolger, 2008, for related results).…”
Section: An Interpersonal Perspectivementioning
confidence: 99%
“…As illustrated in the Manhattan effect, relationship-oriented individuals may not always be generous to their partner and may impose constraints of freedom, but these gestures can be desired as reassurance that they are committed to maintaining the relationship even when confronting obstacles. In contrast, although partner-oriented individuals may support their partner's personal interests across circumstances without expectations of reciprocation, their partner may feel guilty if he or she fails to reciprocate (e.g., Buunk & Schaufeli, 1999;Gleason, Iida, Bolger, & Shrout, 2003;Uehara, 1995). In addition, because relationship protection is so strongly tied to relationship commitment, individuals may see partner-orientation over relationship-orientation as a cue that a partner simply isn't committed, The Manhattan Effect 57 as illustrated toward the beginning of Manhattan, when Isaac enthusiastically supports Tracy's studyabroad opportunity.…”
Section: Additional Directions For Future Researchmentioning
confidence: 99%